Bi- and Multistatic SAR: Potentials and Challenges - Krieger, Gerhard; Fiedler, Hauke; Moreira, Alberto (European Conference on Synthetic Aperture Radar (EUSAR), 2004)
Bi- and multistatic synthetic aperture radar (SAR) operates with distinct transmit and receive antennas which are mounted on separate platforms. Such a spatial separation has several operational advantages which will increase the capability, reliability and flexibility of future SAR missions. We will introduce various spaceborne bi- and multistatic SAR configurations and compare their potentials for different applications like frequent monitoring, wide swath imaging, scene classification, single-pass cross-track interferometry or resolution enhancement.
DLR Import::2019-04-03